Multi Case Analysis on The Development of Fact-Checking Organizations in Indonesia - Rudi Hartanto; Irma Garnesia; Detta Rahmawan (Universitas Padjadjaran, 2022)
The network of fact-checking organizations has expanded widely, and these organizations are seen as one of the important elements in the efforts to tackle the spread of disinformation, misinformation, or hoax in the society. Although the number of fact-checking organizations in all parts of the world continue to increase, scholarly studies which tries to capture the presence of fact-checking practices in Global South Countries, including Indonesia are still limited. This study uses a multi-case study method to analyze the development of fact-checking practices carried out by six organizations in Indonesia which already certified by the International Fact-Checking Network (IFCN) namely: Liputan6, Suara.com, Tirto.id, Kompas.com, Tempo.co, and MAFINDO. Since fact-checking initiatives became popular about six years ago in Indonesia, we discovered that Indonesian fact-checking organizations have grown and strengthened their presence nationally, as well as engaged with various networks of global organizations that leading the ongoing fight against hoax. However, Indonesian fact-checking organizations are still facing several challenges in the context of standardizing fact-checking methodologies, measuring and evaluating the “impact” of their fact-checking activities and related to the management of fact-checking resources. While this study attempts to contribute an overview of Indonesian fact-checking organizations, further studies on fact-checking initiatives with various methodological approaches are still needed to comprehensively look at the role of fact-checking organizations in Indonesia.